FROM TALENT MANAGEMENT TO RETENTION INTENTION: THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT IN STATE-OWNED BANKS - adwi, adwi; Halim, Ade Imam Muttaqien; Hasan, Reski Auliany (Journal of Business Studies and Management Review, 2026)
This study examined how talent management retained state-owned bank employees through employee engagement. The study addressed a theoretical problem in human resource management: formal talent management systems are frequently assumed to increase retention directly, yet employees may remain only when those systems create psychological attachment to work and the organization. Using a quantitative explanatory design, survey data were collected from 136 employees of state-owned banks in Southeast Sulawesi, Indonesia. Talent management was measured through talent attraction, talent selection, talent development, career management, and retention strategy, while engagement and retention were measured as work-related psychological and behavioral intentions. The data were analyzed using partial least squares structural equation modeling. The results showed that talent management strongly increased employee engagement, and employee engagement significantly increased employee retention. However, talent management did not have a significant direct effect on employee retention. The mediation test confirmed that employee engagement fully explained the relationship between talent management and retention. The study contributes to talent management research by showing that retention is not produced by formal human resource practices alone but by the psychological engagement generated by those practices. For state-owned banks, the key managerial implication is that talent programs should be designed as engagement-building systems rather than merely administrative career or training programs.